A moulting population of non-breeding Mute Swans with special reference to flight-feather moult, feeding ecology and habitat selection - Mathiasson, Sven (Wildfowl, 1973)
The build-up of the moulting numbers at the moulting ground and their decline followed a regular, gradual curve. This implies a clear time relation between arrival and departure. Individual swans started to moult about 30 days after the arrival, this span reducing to half at the later part of the influx period. Governing factors must include population density, available food supplies and hormonal condition. Males start their moult somewhat prior to the females. The swans regained the ability to fly 3-4 weeks before the flight feathers achieved full length. The rate of departure seems to be dependent on population density and available food supplies. The swans shifted between haunts in relation to changed food supplies. The main food was Zostera during summer and early autumn, while Ulva was taken later. The swans totally eliminated Ulva in certain areas. The moulting population consumed 425 metric tons, mainly of Zostera, but also some Ulva.